Increasing Economic Opportunities of Women in the APEC - Lucita Lazo (Philippine Institute for Development Studies (PIDS), 2015)
The paper argues for increasing women's economic opportunities in the APEC region and states that women's participation in the economy is skewed toward micro and small enterprises and they are mostly self-employed entrepreneurs in the informal economy. It summarizes the challenges commonly encountered by women entrepreneurs in the APEC economies and recommends actions to address these at the Philippine economy level and at the APEC regional level.
Keywords: 330; APEC; Philippines; informal economy; women; micro and small enterprises